Path follower mobile robot using PID controller - Muhammad, Mazlan (2008)
This project is about path follower mobile robot using PID Controller. As we know the PID controller is a generic control loop feedback mechanism widely used in industrial control system. The controller corrects the error that makes the mobile robot moving out of track. This project concentrates in the development path follower mobile robot which is moving in square path with straight line and turn 90 degree and integrating the PID Controller into steering path for the path follower mobile robot to make the mobile robot moving smooth straight line and turning 90degree. At the end of this project also discuss about the comparison between controllers that could integrate into the mobile robot system.